Aqueous-phase reactions occurred in the PM2.5 cumulative explosive growth during the heavy pollution episode (HPE) in 2016 Beijing wintertime. Issue 1 (1st January 2019) - Wu, Lingyan; Sun, Junying; Zhang, Xiaoye; Zhang, Yangmei; Wang, Yaqiang; Zhong, Junting; Yang, Yun
Abstract: A heavy pollution episode (HPE) that lasted for seven days occurred over the North China Plain in December 2016. An in situ Ambient Ion Monitor was applied to analyze the chemical composition of PM2.5 (fine particulate matter with diameters less than 2.5 µm) and gaseous HONO concentration during that event. A representative explosive growth in the pollution cumulative stage was selected to investigate the pollution mechanism during the HPE in Beijing. PM2.5 cumulative explosive growth processes were observed to occur commonly under high relative humidity (RH) condition. Our results demonstrated that the aqueous-phase oxidation of SO2 by NO2 to sulfate could contribute to the cumulative explosive growth. Nitrate produced by secondary formation was another factor in the growth of PM2.5. Depending on the relative humidity, temperature, and chemical species, the deliquescence relative humidity was calculated to 82%, 81%, and 83% for (NH4 )2 SO4, NH4 NO3, and NH4 Cl, respectively. The preexisting PM2.5 surface changed from solid to liquid when RH > 81%. Coincidentally, both the sulfur oxidation ratio (SOR) and reaction product HONO displayed an evident exponential relationship with RH and increased more quickly when RH was larger than 80%. In addition, sufficiently excessive NO2 made the aqueous-phase oxidation of SO2 efficiently proceed even at relative low SO2 concentrations (below 15 µg m −3 ). Potential H + in the reactions was neutralized by NH3, resulting in fully neutralized PM2.5 during HPE. The chemical evolution of these reactions was discussed in detail in this study.